Motor Development in Malnourished Children in Indonesia - Yasuhide Nakamura; Masroel Siregar (Indonesian Pediatric Society, 1998)
Severe protein-energy malnutrition during infancy is closely related to physical growth and mental development. Very few reports mention the effects on motor development of mildly to moderately malnourished infants. Our study was conducted to clarify the relationship between malnutrition and motor development during infancy. We examined 1,065 children at Posyandu (Integrated Service Posts) in North Sumatera, Indonesia. Motor development, such as sitting and walking, was significantly more delayed in malnourished children than in well-nourished children. Parachute reaction showed no significant differences between well-nourished and malnourished children. Parachute reaction is a very simple technique and can differentiate between children with cerebral-palsy and malnourished children unable to walk. It might be one of the most appropriate technologies for use at the primary care level.